2005
DOI: 10.2527/2005.834786x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationship between milk score and litter weight for Targhee, Columbia, Rambouillet, and Polypay sheep1

Abstract: This study was conducted to evaluate the relationship between milk score (MS) and litter weight at 70 d (LW) for four sheep breeds in the United States. Milk score is a subjective measure of milk production used to assess milk production of range ewes when milk yield cannot be quantitatively determined. Variance components for MS and LW were estimated for each of Targhee, Columbia, Rambouillet, and Polypay breeds. Data collected from 1990 through 2000 at the U.S. Sheep Exp. Stn. in Dubois, ID, were analyzed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
(19 reference statements)
2
5
0
Order By: Relevance
“…According to their study, direct heritability was 0.06, which is close to the result of the current study for TWW1 (0.07). The low estimates of direct heritability for TWW performances in our study were in agreement with the literature results reported in several studies in sheep (Snyman et al, 1997;Bromley et al, 2001;Cloete et al, 2004;Sawalha et al, 2005).…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…According to their study, direct heritability was 0.06, which is close to the result of the current study for TWW1 (0.07). The low estimates of direct heritability for TWW performances in our study were in agreement with the literature results reported in several studies in sheep (Snyman et al, 1997;Bromley et al, 2001;Cloete et al, 2004;Sawalha et al, 2005).…”
Section: Discussionsupporting
confidence: 95%
“…The estimates of genetic correlations among total weight weaned (ranging from 0.54 to 0.75 in the present study) were within the range of 0.07 to 0.88 in Colombia sheep and 0.49 to 0.98 in Targhee sheep reported by Okut et al (1999) between young, middle and old age classes of ewes. Also, they were in accordance with the estimates of 0.61 (between TWW1 and TWW2) and 0.79 (between TWW1 and TWW3) in Afrino sheep and 0.62 (between litter weight at 70 days at first and second parities) in Rambouillet sheep reported by Snyman et al (1997) and Sawalha et al (2005), respectively. The results of the current study for the estimates of residual correlations were not consistent with the findings of Okut et al (1999), Bromley et al (2001) and Sawalha et al (2005) who reported ranges of estimates of − 0.13 to 0.00 among three age classes of ewes, − 0.03 to 0.00 between litter weight weaned and birth weight, and − 0.03 to 0.11 for litter weight for first and second parities in different breeds of sheep.…”
Section: Discussionsupporting
confidence: 92%
“…Reported estimates direct heritability for different sheep breeds range from 0.00 to 0.38 for lamb birth weight, 0.025 to 0.49, for weaning weight (Babar et al, 2003;Bahreini et al, 2007;Duru and Koyuncu, 2005;Hanford et al, 2006;Ligda et al, 2000;Maria et al, 1993;Carrillo and Segura, 1993;Hanford et al, 2003;Nakagawa et al, 2005;Noter and Hough, 1997;Ozcan et al, 2005;Reale et al, 1999;Sawalha et al, 2005;Szwaczkowski et al, 2006;Tosh and Kemp, 1994;Wuliji et al, 2001;Wyk et al, 2003) and 0.12 to 0.25 for yearling weights (Reale et al, 1999;Ozcan et al, 2005), and 0.11 to 0.33 for average daily gain (Carrillo and Segura, 1993;Maria et al, 1993;Noter and Hough, 1997;Ozcan et al, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…Age and parity of the ewe significantly affect reproductive traits, most notably litter size (Haresign 1985;Waldron and Thomas 1992), lactation (Torres-Hernandez and Hohenboken 1980; Snowder and Glimp 1991;Snowder et al 2001a;Sawalha et al 2005) and litter weight weaned (Ercanbrack and Knight 1985;Okut et al 1999). A study by Fogarty et al (1985) reported the heritability estimate for litter weight weaned increased across parities, noting that both the phenotypic and direct genetic variances increased but the proportional increase in the direct genetic variance was greater.…”
Section: Genetic Variance Estimates Associated With Litter Weight Weanedmentioning
confidence: 99%
“…A subjective milk score recorded within 24 h of parturition has a high genetic correlation with 120-days litter weight weaned in four sheep breeds and ranged from 0.77 to 1.00 (Snowder et al 2001b). However, Sawalha et al (2005) used the same dataset as Snowder et al (2001b) and reported that genetic correlations between subjective milk score and litter weight weaned would be lower (ranging from 0.15 to 0.68) if weaning occurred at a younger age of 70 days.…”
Section: Genetic Correlations With Litter Weight Weanedmentioning
confidence: 99%